KAJIAN TINGKAT KONTINUM KAPITAL SOSIAL FAKULTAS TARBIYAH DAN KEGURUAN DALAM MENGWUJUDKAN VISI, MISI DAN TUJUAN UIN SULTAN SYARIF KASIM RIAU - Ansharullah Ansharullah (Lembaga penelitian dan pengabdian kepada Masyarakat, 2015)
The aims of this research are to find out the level of Social Capital Continuum and the what factors affecting the level of Social Capital Continuum employees and lecturers in the Faculty of Education and Teacher Training UIN Suska Riau. The subjects were employees and lecturers in the Education and Teacher Training UIN Suska Riau and the object is a levels of Social Capital Continuum of employees and lecturers in the Faculty Education and Teacher Training UIN Suska Riau. The population is all the structural employees (administration) consist of 44 people and functional (lecturer) of 158 Faculty of MT and Teaching UIN Suska Riau with the sampling method consists of two ways, namely variable structural employees using total sampling method and sampling methods for functional variables (lecturer) using purposive sampling method. While research method used is descriptive qualitative method. The result of this research shows that the level of social capital continuum structurally and cognitive categories of employees and lecturer at the Faculty of Education and Teacher Training UIN Suska Riau in achieving the vision, mission and goals of the organization are in the category of Social Capital Maximum with the percentage of 79.90%, due to ranging between 76% - 100%.